Effects of Red Imported Fire Ants (Solenopsis invicta) on the Species Structure of Ant Communities in South China - Yong Yue Lu (Sociobiology, 2014)
We evaluated the effects of invasive red imported fire ants (RIFAs), Solenopsis invicta Buren, on native ant communities at three habitats in South China. By using paired control and treatment plots, the change in diversity and community structure of native ants due to the invasion of red imported fire ants could be observed. Ant species richness was reduced by 46 and 33% at RIFA-infested lawn and pasture habitats, respectively; however, the ant species richness in the lichee orchard was not affected by red imported fire ants. Our results indicated that red imported fire ants became one of several dominant species or the only dominant species in all three habitats in South China.